Hacienda Retes: Cultural heritage and identity aporias - Guzmán Juárez, Miguel (2021)
The system of haciendas -farms- located at the Chancay valley represented a complex phenomenon in the management of the territory, in the consolidation of an architectural typology and in the implications of the social relations system, which was established since the first decades of the foreign conquest, approximately in the second third of the sixteenth century. The spatial reorganization of the lower- and middle-valleys was designed in connection with the already existing Andean planning and infrastructure, therefore, this research is not only about the haciendas, but also about certain continuities and recreations specially observed in the layouts of these new human settlements. On a field work and contemporary registry of the hacienda houses that still exist, the importance and the architectural hierarchy held are valued.  Among them, Caqui, Palpa, Huando or Retes stand out, and others. But the Hacienda Retes has a special significance for being part of the spaces and buildings which were used to host the work of the national independence carried out two hundred years ago. A heritage of the beginning of the Republic that unfortunately, today deal with abandonment, deterioration, and indifference, disguised of identity aporias.